ANALISIS DAYA TARIK WISATA PANTAI TANJUNG KARANG, PALU, SULAWESI TENGAH - RENDY WIJAYA, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Research on the analysis of the potential tourist attraction of Tanjung Karang Beach in Palu City, Central Sulawesi has the aim of understanding the potential of Tanjung Karang Beach tourist attraction in Palu City, and understanding the direction of development of the potential development of Tanjung Karang Beach tourist attraction in Palu City. This study uses observational research in the field carried out directly and interviews with the management department as well as visits and analysis of secondary data obtained by agencies, government and private institutions in Palu City. Analytical techniques take advantage of internal as well as external potentials and the union of both. The SWOT analysis is to understand the advantages, disadvantages, possibilities and risks obtained from the attractiveness of coastal tourism and utilize it as a strategy formation and direction of future development. The results obtained from this study explain that Tanjung Karang Beach has the same potential between internal and medium. The beach tourism attraction that is activated in development is Tanjung Karang Beach based on the highest potential assessment. Tanjung Karang Beach is the main beach in Palu City that most come because it becomes a charm for rescue even though its location is quite far, which is about 32 km from Palu City. The development of tourist attractions that can be carried out through maximizing the land around the coast, as well as developments in complementary rides and facilities, completing facilities and infrastructure that do not yet exist through the implementation of cooperation with the city government or the private sector concerned.